A REVISION OF ISEILEMA (GRAMINEAE) IN MALESIA - J. F. VELDKAMP (BRIN Publishing (Penerbit BRIN), 2016)
VELDKAMP, J. F. 2016. A revision of Iseilema (Gramineae) in Malesia. Reinwardtia 15(2): 123 – 127. — There are three very rare and localized species in Malesia; one from Java is new. Notes on some other Southeast Asian species are given.